Parasites in the Digestive Tract of Lion (Panthera leo) at the Safari Park of Gurun Putih Lestari Jantho, Aceh Besar - Fajri Dwitama; Razali Daud; Arman Sayuti; Yudha Fahrimal (Journal of Applied Veterinary Science And Technology, 2025)
Background: Parasitic infections in wild animals housed in captivity pose a threat to the success of animal conservation endeavors. Factors such as environmental contamination, abrupt alterations in ecological circumstances, and spatial constraints render captive animals vulnerable to stress, consequently compromising their immune systems. These infections have a notable impact on the host. Furthermore, not only captive animals but also personnel, visitors, and the public at large can be at risk of contracting parasites that have the potential to infect various species. Purpose:  This study seeks to ascertain the occurrence of gastrointestinal endoparasitic infections in lions housed at the Gurun Putih Lestari Safari Park in Jantho, district of Aceh Besar. Method: Samples were collected from five lions housed at Gurun Putih Lestari Safari Park in Jantho, district of Aceh Besar. The sampling procedure involved direct collection of lion feces, which were then placed in containers with 10% formalin and labelled accordingly. Sampling was conducted three times at 15-day intervals. The fecal samples were analyzed using four methods: flotation, sedimentation, formol ether, and modified Ziehl-Neelsen method. Results:  The analysis of fecal samples revealed that three adult lions were found to be infected with Toxocara cati, Toxascaris leonina, Ancylostoma spp., and Cystoisospora rivolta, while two lion cubs were solely infected with Toxocara cati and Ancylostoma spp. Notably, the modified Ziehl-Neelsen technique did not detect any gastrointestinal endoparasites. Conclusion: The findings suggest that lions housed at Gurun Putih Lestari Safari Park in Jantho, district of Aceh Besar are infected by gastrointestinal parasites. It is recommended to administer deworming treatment to lions as a preventive measure against a surge in parasitic infection among the lion population.